The Educational cooperativism and mutualism and its social dimension: Educational, cultural and community impact of cooperation and reciprocity experiences during preventive confinement - Gallo, Griselda María; Hepp, Mabel Erika (Cooperativismo & Desarrollo, 2022)
This article is the result of a qualitative approach research process through bibliographic review and with the active participation of the actors of the territory of Córdoba, Argentina. The different experiences around coo-perative learning were studied based on the integral development of its inhabitants, contributing significantly from the perspective of the objectives of sustainable development. Finally, scientific, purposeful and transfor-ming knowledge with a high socio-educational, socio-cultural and socio-community impact is provided, from a holistic and interdisciplinary perspective, which results in new lines of inquiry.
Keywords: cooperativism and educational mutualism; school cooperative; school mutual; sustainable development objectives